Does institutional innovation of patent financing ease corporate financing woes? Evidence from patent collateral and patent insurance policy - Xiaoxi Li; Qinger Zhong; Guochao Yang; Pingui Rao (China Journal of Accounting Studies, 2024)
This paper employs patent collateral data from China’s State Intellectual Property Office and finds that patent collateral policy increases the use of patents as collateral and corporate debt financing; further, patent insurance policy enhances the effect of patent collateral policy. However, these policies only lead to an increase in corporate short-term debt. Additionally, we document a stronger effect for cities that integrate an effective government and an efficient market, cities where governments provide guarantees to firms, firms with high-quality patents, and financial constrained firms. As a result, increases in corporate short-term debt resulting from patent collateral policy and patent insurance policy lead to higher patent output in the short run, rather than in the long run.